Buckling failure analysis of all-terrain crane telescopic boom section. (November 2015) - Yao, Jia; Qiu, Xiaoming; Zhou, Zhenping; Fu, Yuqin; Xing, Fei; Zhao, Erfei
Abstract: In this research work, a nonlinear structure analysis by the finite element analysis (FEA) was carried out to investigate the failure reason of an all-terrain crane telescopic boom. An overall simplified model consisting of telescopic boom and luffing jib was established by beam element, and analyzed using geometric nonlinear static method. A local detailed model consisting of the 4th and 5th telescopic boom section (TBS) was established by shell and solid element, and analyzed using geometric nonlinear and contact nonlinear static method. The result of the overall simplified model FEA indicated that the boom strength met the design criteria, and the 5th TBS of local detailed model occurred stress wrinkle. Structure experiment was designed based on the boom load characteristics in accident and analyzed using nonlinear static method and explicit dynamic method; the connection of load, boom buckling failure and stress wrinkle was studied. The result indicated that the accident was caused by elastic buckling. When the telescopic boom stress state changed from continuous state to wrinkle state, the buckling occurred. So the critical buckling state characteristic was stress wrinkle. Highlights: The failure reason of an all-terrain crane telescopic boom section was studied. The telescopic boom section is a thin-walled structure with special cross-section. Dynamic test, nonlinear implicit static and explicit dynamic FEA were used. The connection of stress wrinkle and buckling was discussed.